A CRITICAL DISCOURSE ANALYSIS OF YESUNG SUPER JUNIOR’S LANGUAGE USE TO BUILD A DIGITAL CONNECTION WITH INDONESIAN FANS - Annisa Dhea Nurbaity, (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Globalization of the Korean entertainment industry (K-pop) has intensified glocalization practices where the artists use local languages of certain culture or country as their communication styles. This aim research is to examine how Yesung, Super Junior member, uses Indonesian language in tweets of his Twitter/X platform as a strategy to build connection with Indonesian fans. Employing Fairclough's Critical Discourse Analysis (CDA) framework, this research will analyse language choices, discursive styles, and affective symbols in Yesung's tweets containing hashtag #Indonesia with Indonesian language. The data will be collected through documentation of 19 tweets within 2016-2024, and will be analysed on three levels: textual, discursive practices, and social practice. It will be uncovered how digital discourse constructs power relations, global identity, and connection strategies by K-pop artists targeting local audiences. The results of this research are expected to give contributions in glocalization, digital linguistics, and cultural representation in social media. Keywords: Critical discourse analysis; K-Pop; Language use; Digital communication; Fan engagement